2013
DOI: 10.1016/j.foreco.2013.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Peat consumption and carbon loss due to smouldering wildfire in a temperate peatland

Abstract: a b s t r a c tTemperate peatlands represent a substantial store of carbon and their degradation is a potentially significant positive feedback to climate change. The ignition of peat deposits can cause smouldering wildfires that have the potential to release substantial amounts of carbon and to cause environmental damage from which ecosystem recovery can be slow. Direct estimates of the loss of carbon due to smouldering wildfires are needed to inform global estimates of the effect of wildfire on carbon dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 36 publications
5
107
1
Order By: Relevance
“…Duff consumption in the field is increased by drought conditions, which would contribute variability on real fires (Davies et al, 2013). In summary, the results presented indicate that, in all cases, the overall ecosystem and mixture of components produces a radiative forcing.…”
mentioning
confidence: 75%
“…Duff consumption in the field is increased by drought conditions, which would contribute variability on real fires (Davies et al, 2013). In summary, the results presented indicate that, in all cases, the overall ecosystem and mixture of components produces a radiative forcing.…”
mentioning
confidence: 75%
“…1), which plays an important role in the estimation of soil carbon emission. The DOB and critical MC for extinction ðMC Ã ex Þ at the vertical downward (or indepth) spread of peat fires have been investigated by various experiments (Benscoter et al 2011;Watts 2012;Davies et al 2013;Zaccone et al 2014) and numerical simulations Rein 2015, 2016a;Yang et al 2016). Recently, laboratory experiments on the horizontal fire spread over a shallow peat sample showed that the spread rate decreased with MC but increased with the forward wind speed (Huang et al 2016;Prat-Guitart et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These gases contribute significantly to global emissions of greenhouse gases . Smouldering peat fires also affect the roots of vegetation close to the surface, often causing lethal plant damage and habitat losses (Miyanishi and Johnson 2002;Page et al 2002;Davies et al 2013). The landscape after a peat fire is often heterogeneous, as peat is consumed in irregular patches (Shetler et al 2008).…”
Section: Introductionmentioning
confidence: 99%